Hubungan Umur dan Gravida dengan Kejadian Kekurangan Energi Kronik pada Ibu Hamil di Puskesmas Lau Baleng Kecamatan Lau Baleng Tahun 2023 - Evalilis Br Munthe; Nur Azizah; Rosmani Sinaga (PPNI UNIMMAN, 2024)
Background: Chronic Energy Deficiency (CED) in pregnant women is a health problem that can affect the mother and fetus. Age and number of pregnancies (gravida) are thought to be related to the incidence of CED. This study aims to analyze the relationship between age and number of pregnancies with the incidence of CED in pregnant women at the Lau Baleng Health Center, Lau Baleng District, in 2023.Methods: This study used an analytical design with a cross-sectional approach. The study sample consisted of 56 pregnant women selected by purposive sampling. Data were collected through interviews and measurements of the Upper Arm Circumference (MUAC), then analyzed using the chi-square test.Results: The results showed that 23.2% of respondents experienced CED. Bivariate analysis showed a significant relationship between age and the incidence of CED (p = 0.004), where mothers aged <20 years or >35 years had a higher risk of experiencing CED than mothers aged 20-35 years. In addition, there is a significant relationship between the number of pregnancies (gravida) and the incidence of CED (p = 0.004), where mothers with a history of more than five pregnancies (grandemultigravida) have the highest prevalence of CED (62.5%). Conclusion: The age of pregnant women and the number of pregnancies have a significant relationship with the incidence of CED. Therefore, prevention efforts are needed through nutritional education for pregnant women, especially in the at-risk age group and mothers with high parity, to reduce the incidence of CED.